Bacterial vaginosis: Etiology and modalities of treatment-A brief note - Nikhil Kumar; Beauty Behera; Sai S Sagiri; Kunal Pal; Sirsendu S Ray; Saroj Roy (Wolters Kluwer Medknow Publications, 2011)
A large women population of the world is suffering from a vaginal infection commonly known as bacterial vaginosis. The disease is associated with the decrease in the lactobacilli count in the vagina. Till date, there is a lack of full proof treatment modalities for the cure of the disease. The treatment includes the use of antimicrobials and/or acidifying agents and probiotics, either separately or in combination. This note discusses about the etiology and the various present-day modalities of treatment of bacterial vaginosis.